Analytical study of hydraulic and mechanical effects on tide-induced head fluctuation in a coastal aquifer system that extends under the sea - Guarracino, Luis (2012)
Head response to sea level fluctuations has been extensively used for characterizing coastal aquifers. When the aquifer is semiconfined and extends for a certain distance . D under the sea, head response results from the superposition of two types of effects: hydraulic (i.e., ground water flow connection through aquifer and aquitard) and mechanical (induced by tidal loading onto the sea floor). Solutions are available for this problem that has been analyzed before, but only for . D zero or infinity. These solutions do not allow analyzing aquifer systems that extends for a finite . D, or identifying them, which is critical for coastal aquifer management. We derive an exact analytical solution that describes separately the mechanical and hydraulic effects. The proposed analytical solution is a generalization of most of existing analytical solutions. A simpler approximate analytical solution is also obtained for soft aquitards with low permeabilities. We find that the impact of the hydraulic component of the aquitard and the mechanical effects in the total head fluctuation at the shoreline is significant, but not very sensitive to the properties of the aquitard. The amplitude of these fluctuations relative to that of the sea tide ranges approximately between 1 (small . D) and 0.5 (large . D). This implies that aquifer penetration under the sea can indeed be identified if it is below a certain threshold, beyond which the system responds as if . D was infinity. Surprisingly, the time lag is close to zero regardless of hydraulic parameters of the aquifer system.